MOVEMENT OF CHLORIDE INTO A WELL-DRAINED SOIL - Yulnafatmawita Yulnafatmawita (Jurnal Solum, 2004)
Chemical leaching from soil surface will cause groundwater pollution. Researches showed spatial correlation of the leaching chemicals. Based on the fact, a filed research was conducted at Maury silt loam soil (fine, mesic, mixed, Typic Paleudalf) to evaluate spatial variations of anion movement, in tis case was Cl, into and below rooting zone. Source of chloride, SrCl2.6H2O, was evenly distributed on soil surface within a 18 x 18 m2 plot in University of Kentucky Experimental Station, Lexington, Kentucky USA. Soil was sampled for 4 times (after receiving 166, 310, 586, 1085 mm rainfall), in every 10 cm depth for 54 points within the plot. The result showed that Cl- movement did not show spatial model from soil surface into 100 cm profile in every sampling date. Therefore, based on analysis of variance, Cl- concentration was significantly different from one depth to another within one sampling time. Cl- concentration found on the depth of 100 cm was 75, 58, 27, and 15% for sampling time I, II, III, and IV, consecutively. Key Words: groundwater pollution, anion leaching, agricultural chemicals, spatial structure